Genetic Interaction Among Phytochrome, Ethylene and Abscisic Acid Signaling During Dark-Induced Senescence in Arabidopsis thaliana - Ueda, Hiroaki; Ito, Takeshi; Inoue, Ryouhei; Masuda, Yu; Nagashima, Yumi; Kozuka, Toshiaki; Kusaba, Makoto (Frontiers in Plant Science, 2020)
Leaf senescence is induced by various internal and external stimuli. Dark-induced senescence has been extensively investigated, but the detailed mechanism underlying it is not well understood. The red light/far-red light receptor phytochrome B and its downstream transcription factors, PYHTOCHROME INTERACTING FACTORs (PIFs) 4 and 5, are known to play an important role in dark-induced senescence. Furthermore, the senescence-inducing phytohormones, ethylene and abscisic acid (ABA) are reported to be involved in dark-induced senescence. In this study, we analyzed the relationship between ethylene, ABA and PIFs in dark-induced leaf senescence. A triple mutant of the core ABA signaling components; SNF1-related protein kinases 2D (SRK2D), SRK2E, and SRK2I, displayed an ABA insensitive phenotype in ABA-induced senescence, whilst the ethylene insensitive mutant ein2 demonstrated low sensitivity to ABA, suggesting that ethylene signaling is involved in ABA-induced senescence. However, the pif4 pif5 mutant did not display low sensitivity to ABA, suggesting that PIF4 and PIF5 act upstream of ABA signaling. Although PIF4 and PIF5 reportedly regulate ethylene production, the triple mutant ein2 pif4 pif5 showed a stronger delayed senescence phenotype than ein2 or pif4 pif5, suggesting that EIN2 and PIF4/PIF5 partially regulate leaf senescence independently of each other. While direct target genes for PIF4 and PIF5, such as LONG HYPOCOTYL IN FAR-RED1 (HFR1) and PHYTOCHROME INTERACTING FACTOR 3-LIKE 1 (PIL1), showed transient upregulation under dark conditions (as is seen in the shade avoidance response), expression of STAY GREEN1 (SGR1), ORESARA1 (ORE1) and other direct target genes of PIF5, continued to increase during dark incubation. It is possible that transcription factors other than PIF4 and PIF5 are involved in the upregulation of SGR1 and ORE1 at a later stage of dark-induced senescence. Possible candidates are senescence-induced senescence regulators (SIRs), which include the NAC transcription factors ORE1 and AtNAP. In fact, ORE1 is known to bind to the SGR1 promoter and promotes its expression. It is therefore inferred that the phytochrome-PIF pathway regulates initial activation of senescence and subsequently, induced SIRs reinforce leaf senescence during dark-induced senescence.